The Priority of Suffering Over Life. How to Accommodate Animal Welfare and Religious Slaughter - Zuolo, Federico (Les ateliers de l'éthique / The Ethics Forum, 2014)
Most contemporary Western laws regarding the treatment of animals in livestock farming and animal slaughter are primarily concerned with the principle that animal suffering during slaughter should be minimized, but that animal life may be taken for legitimate human purposes. This principle seems to be widely shared, intuitively appealing and capable of striking a good compromise between competing interests. But is this principle consistent? And how can it be normatively grounded? In this paper I discuss critically this principle (the priority of the minimization of animal suffering over animals’ right to life). I argue that this principle can be justified on the ground of respect for the value commitment toward animal welfare, which is held by many people. The advantage of this perspective is its inclusiveness: it can justify without contradiction the principle at stake and allow for the admissibility of religious slaughter while promoting animals’ interest in not suffering. This justification also has the advantage of being compatible with the cultural and religious pluralism of contemporary societies.